2020
DOI: 10.1111/gcb.15248
|View full text |Cite
|
Sign up to set email alerts
|

Total ecosystem carbon stocks at the marine‐terrestrial interface: Blue carbon of the Pacific Northwest Coast, United States

Abstract: The coastal ecosystems of temperate North America provide a variety of ecosystem services including high rates of carbon sequestration. Yet, little data exist for the carbon stocks of major tidal wetland types in the Pacific Northwest, United States. We quantified the total ecosystem carbon stocks (TECS) in seagrass, emergent marshes, and forested tidal wetlands, occurring along increasing elevation and decreasing salinity gradients. The TECS included the total aboveground carbon stocks and the entire soil pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…Recent studies of the U.S. west coast and of conterminous U.S. tidal wetlands allow for comparison with salt marsh data collected here. Much like with seagrass meadows, California salt marsh carbon storage was also higher than previous estimates from the U.S. west coast (Kauffman et al, 2020;Table 3). Both the data presented here as well as those from Kauffman et al (2020) (Table 3) were collected from similar marsh zones and species compositions, reducing some potential for these factors to result in the observed differences in carbon stocks.…”
Section: Global and Regional Comparisonsmentioning
confidence: 46%
See 2 more Smart Citations
“…Recent studies of the U.S. west coast and of conterminous U.S. tidal wetlands allow for comparison with salt marsh data collected here. Much like with seagrass meadows, California salt marsh carbon storage was also higher than previous estimates from the U.S. west coast (Kauffman et al, 2020;Table 3). Both the data presented here as well as those from Kauffman et al (2020) (Table 3) were collected from similar marsh zones and species compositions, reducing some potential for these factors to result in the observed differences in carbon stocks.…”
Section: Global and Regional Comparisonsmentioning
confidence: 46%
“…Much like with seagrass meadows, California salt marsh carbon storage was also higher than previous estimates from the U.S. west coast (Kauffman et al, 2020;Table 3). Both the data presented here as well as those from Kauffman et al (2020) (Table 3) were collected from similar marsh zones and species compositions, reducing some potential for these factors to result in the observed differences in carbon stocks. Previous work has found that high-marsh zone sediments are likely to contain greater OC than mid-and lower-marsh zones, and that less inundation can facilitate increased root productivity and increased OC (the sites presented here would be considered 'lower-marsh zones') (Blum, 1993;Connor et al, 2001;Zhou et al, 2007).…”
Section: Global and Regional Comparisonsmentioning
confidence: 46%
See 1 more Smart Citation
“…Hereafter, NPCTR will refer to these two subregions. Within the NPCTR, large and long-lived conifers, abundant peatland ecosystems, and deep soils store some of the highest amounts of C globally (combined above- and belowground, more than 1000 megagrams [Mg] per hectare [ha]; Smithwick et al 2002 , McNicol et al 2019 , Kauffman et al 2020 ). The landscape has been largely shaped by several episodes of glaciation, combined with uplift and erosional processes, leading to a complex pattern of islands, incised coastal mountain ranges, fjordlands, wide glacial valleys, and lowlands.…”
Section: Ecoregion Descriptionmentioning
confidence: 99%
“…Salt marsh carbon stocks are similarly understudied in western North America, with published carbon stock data from only four estuaries in the region and very minimal spatial coverage and analyses performed in three of these locations (Brevik and Homburg, 2004;Callaway et al, 2012;Kauffman et al, 2020;Patrick and DeLaune, 1990). Existing analyses of North American freshwater wetlands and salt marshes are typically dominated by studies along the east coast (Nahlik & Fennessy, 2016;Wilkinson et al, 2018; with the exception of Holmquist et al 2018).…”
Section: Carbon Stock Assessments and Their Significancementioning
confidence: 99%